Mastering AutoCAD 2017 and AutoCAD LT 2017 - Omura, George; Benton, Brian C. (Autodesk Official Press/Sybex, 2016)
The bestselling guide to AutoCAD, updated and expanded with new video instruction Mastering AutoCAD 2017 and AutoCAD LT 2017 is the premier guide to the world's leading CAD program. With clear explanation, focused examples, and step-by-step instruction, this guide walks you through everything you need to know to use AutoCAD 2017 and AutoCAD LT 2017 effectively. From basic drafting tools to 3D modeling, this book leaves no stone unturned in exploring the full repertoire of AutoCAD capabilities. Hands-on instruction allows for more productive learning, and over an hour's worth of video provides clarification of crucial techniques. Effective as both a complete tutorial and a dip-in reference, the broadly-applicable concepts and instructions will appeal to AutoCAD users across industries and abilities. This new edition has been thoroughly updated to align with the software's latest features and capabilities, giving you a one-stop resource for getting up to speed. AutoCAD is the leading software for 2D and 3D technical drawings, and AutoCAD LT makes the software's tremendous functionality more accessible for smaller businesses and individuals. This guide shows you how to take full advantage of this powerful design platform, with expert guidance every step of the way.-Get acquainted with the interface and master basic tools -Utilize hatches, fields, cures, solid fills, dynamic blocks, and more -Explore 3D modeling and imaging for more holistic design -Customize the AutoCAD workflow to suit your needs Whether you're learning AutoCAD for the first time, upgrading from a previous version, or preparing for a certification exam, you need a thorough reference designed for the way professionals work. Mastering AutoCAD 2017 and AutoCAD LT 2017 is your ideal guide, with complete tutorials, video instruction, and expert advice.